PRINCIPLES OF STUDYING THE LIFE AND WORK OF N. A. NEKRASOV IN ACADEMIC LYCEUMS BASED ON MODERN PEDAGOGICAL TECHNOLOGIES - Yusupiy Mehribon Amindzhanovna (International Journal of Literature and Language Studies, 2026)
This article examines the theoretical and methodological foundations of studying the life and works of N. A. Nekrasov in academic lyceums of the Republic of Uzbekistan through the use of modern pedagogical technologies. The necessity of transitioning from the traditional informational and reproductive model of education to competency-based, learner-centered, and communicative-activity approaches is substantiated. The article presents the results of a methodological analysis of the effectiveness of interactive technologies, including the case-study method, critical thinking development technology, problem-based learning, digital educational platforms, and project-based learning in the study of the Russian poet's works. A model for the formation of students' literary competence is proposed, based on the integration of digital tools, analytical work with literary texts, and interdisciplinary connections.